The Influence of CSR, Environmental Investment, Environmental Performance, Environmental Disclosure and Financial Performance (Empirical Study on Manufacturing Companies Registered on the IDX) - Siregar, Nella Astria; Zoraya, Intan (Universitas Negeri Semarang, 2025)
This study aims to evaluate the influence of Corporate Social Responsibility (CSR), environmental investment, environmental performance, and environmental disclosure on the financial performance of companies. The research is motivated by the crucial role of sustainability practices and corporate social responsibility in supporting financial outcomes, particularly in the manufacturing sector, which has a significant environmental impact. A quantitative approach was employed using multiple linear regression analysis. The sample consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023, with a total of 195 observations. The findings reveal that, simultaneously, all four independent variables significantly affect financial performance. Partially, CSR and environmental performance make a significant positive contribution to enhancing financial performance, while environmental investment shows a negative effect and environmental disclosure has a significant negative impact on financial performance. The implication of this study is that companies need to carefully assess the effectiveness of their environmental investment allocation and disclosure strategies to ensure that they create added value for financial performance without reducing their commitment to sustainability.